2018
DOI: 10.1101/335919
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multimodal transcriptional control of pattern formation in embryonic development

Abstract: Predicting developmental outcomes from regulatory DNA sequence and transcription 17 factor patterns remains an open challenge in physical biology. Using stripe 2 of the even-skipped 18 gene in Drosophila embryos as a case study, we dissect the regulatory forces underpinning a key 19 step along the developmental decision-making cascade: the generation of cytoplasmic mRNA 20 patterns via the control of transcription in individual cells. Using live imaging and computational 21 approaches, we found that the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
110
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(121 citation statements)
references
References 96 publications
(176 reference statements)
9
110
2
Order By: Relevance
“…Calculation of the autocorrelation function in traces from these nuclei suggest very slow transcriptional dynamics ( Fig. S4ED) (Desponds et al 2016;Lammers et al 2018), which would be consistent with one long period of activity as opposed to overlapping short bursts. This fits with a model where promoters can exist in a permissive active state, during which many "convoys" of polymerase can be fired without the promoter reverting to a fully inactive condition (Tantale et al 2016).…”
Section: Priming Of Enhancers Sensitizes the Response To Nicdmentioning
confidence: 71%
See 4 more Smart Citations
“…Calculation of the autocorrelation function in traces from these nuclei suggest very slow transcriptional dynamics ( Fig. S4ED) (Desponds et al 2016;Lammers et al 2018), which would be consistent with one long period of activity as opposed to overlapping short bursts. This fits with a model where promoters can exist in a permissive active state, during which many "convoys" of polymerase can be fired without the promoter reverting to a fully inactive condition (Tantale et al 2016).…”
Section: Priming Of Enhancers Sensitizes the Response To Nicdmentioning
confidence: 71%
“…4E). In most previous enhancers analyzed in this way, the off period is the most affected, leading to changes in the bursting frequency (Fukaya et al 2016;Fritzsch et al 2018;Lammers et al 2018). However, when we quantified the effect from different doses of NICD on sim in the ME we found that the bursting length consistently increased with higher amounts of NICD whereas the off period between bursts remained constant ( Fig.…”
Section: Notch Activity Tunes Transcription Burst Sizementioning
confidence: 83%
See 3 more Smart Citations